Analisis Distribusi Dosis pada Treatment Planning System Pasien Kanker Payudara dengan Sumber Foton 6 MV pada Instalasi Radioterapi Rumah Sakit X - Prayoga, Bonifasius Kristo; Riupassa, Robi Dany (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The internship at X Hospital aimed to gain practical experience as a medical physicist over two months, particularly in the treatment planning system activities in the radiotherapy unit. Additionally, this internship aimed to evaluate the Dose Volume Histogram (DVH) and analyze the effectiveness of the isodose lines. The treatment planning system is a simulation of cancer or tumor treatment using radiation with 3D conformal radiotherapy (3D-CRT) techniques. The patient study object was a woman with post-mastectomy breast cancer who was to undergo adjuvant curative therapy. The prescribed dose was 50 Gy, divided into 25 fractions, using a 6 MV photon source. The irradiation was conducted with four fields, gantry angle 129° with collimator angle 270°, 310° with collimator angle 90°, 130° with collimator angle 0°, and 270° with collimator angle 0°, field size 14 x 14 cm, and irradiation distance of 100 cm. The TPS simulation results indicated that the dose received by the Planning Target Volume (PTV) covered more than 90% of the target volume (special treatment), while the dose received by the Organ at Risk (OAR) tended to be below the threshold limit, and the isodose lines ensured optimal radiation dose distribution to the breast cancer target area. This was demonstrated by the DVH curve.